حقوق حیوانات: اسلامی تعلیمات اور مغربی افکار کا تجزیاتی مطالعہ (Al-Qamar, 2020)
In the Qur'an al-Hakim, the study of the phenomena of nature and the human welfare derived from them is mentioned with a considerable frequency. Human life on this planet depends on both non-living elements and living bodies. However, this article is intended to mention only animals, especially pets. From time immemorial man has been able to derive various benefits from animals. For example, it has been getting benefits from milk, meat, manure, manure and fuel, clothing from skins and houses (tents) etc. God, the Lord of Glory, created man and jinn for His worship. And besides, He has commissioned all creatures to serve man. From the Qur'anic teachings and the teachings of the Prophet (peace and blessings of ALLAH be upon him) we find that the rights of human beings and even animals have been defined in Islam. In the supernatural religions we still see these things clearly, while in the non-divine religions which are adorned with human invention, even though the loudest claimants of animal rights know that for the first time in Europe the animal rights legislature built in 1635.
Keywords: Animals; Benefits from Milk; Meat; Manure and Fuel; Clothing from Skins